Knowledge, attitude, and awareness toward autopsy practice among King Saud University medical students - Khaldoon Aljerian; Norah AlHogail; Saud Abdulaziz Alaqeel; Khayyal Mohammed Alderaan; Abdulla Taher Al-Hawamdeh; Hani Jamal Alhudhaif (Wolters Kluwer Medknow Publications, 2023)
Introduction: The present study was undertaken to understand the level of awareness, education, and motivations of medical students toward the practice of autopsy. Methods: We distributed 213 questionnaires among undergraduate medical students. A total of 199 participants gave informed consent to be enrolled in this study and agreed to the anonymous publication of the findings. After data curation, the data were coded and analyzed using structural equation modeling (SmartPLS software). Results: Saudi medical students who studied the autopsy course find a student's ideology to be a determinant variable governing the perception of autopsy performance. Their acquisition of knowledge about autopsy did not suffice to change their attitude toward performing autopsies. However, the students' self-reported awareness positively affects their attitude toward performing autopsy. Conclusions: The students think that autopsy causes neither disfigurement nor disrespect of the cadaver. Nevertheless, the inclusion of a more hands-on approach could help include the "hidden curriculum," i.e., the crucial aspects that escape formal teaching and arise from watching teachers, their attitudes, techniques, and interests. The insights obtained from this study aim to improve and advance forensic studies among medical students in Saudi Arabia.